A novel storage driven granular post denitrification process: Long-term effects of volume reduction on phosphate recovery - Salehi, S.; Cheng, K.; Heitz, Anna; Ginige, M. (Elsevier BV, 2019)
Anoxic granular biomass with enhanced biological phosphorus (P) removal was used in a post-denitrification configuration to concentrate P in wastewater. The study examined the use of anoxic granules to facilitate application of volume reduction to create a P-enriched stream (>100 mg-P/L). The results indicated the importance of maintaining a food to microorganism (F/M) ratio of ~0.124 g-COD/g-MLSS.d to achieve P and nitrogen (N) removal close to 100%. While granulation required a short settling time and a high-volume exchange ratio, biomass wasting was essential to control the F/M ratio to maintain a suitable microbial diversity and abundance. Diversity and abundance were also impacted by volume reduction, but the effect of this was marginal compared with the effect of decreasing F/M ratio. Furthermore, a decrease in the F/M ratio enhanced sedimentation (SVI5decreased from 55.5 to 32.0 mL/g-MLSS) but decreased dewaterability (capillary suction time increased from 15.5 s to 19.4 s). Recovery of P as a concentrated liquor had minimal impact on the bacterial diversity.